Gram-positive Staphylococcus aureus LTA promotes distinct memory-like effects in murine bone marrow neutrophils - Lajqi, Trim; Frommhold, David; Jungwirth, Maylis; Kranig, Simon A.; Pöschl, Johannes; Hudalla, Hannes (Cellular immunology, 2022)
Neutrophils primarily act as first responders in acute infection and directly maintain inflammatory responses. However, a growing body of evidence suggests that neutrophils also bear the potential to mediate chronic inflammation by exhibiting memory-like features. We now asked whether bone marrow-derived murine neutrophils can be primed by lipoteichoic acid (LTA) from gram-positive S. aureus. We found that low-dose (1ng/mL) LTA-priming promoted increased production of pro-inflammatory mediators (TNF-α, IL-6, ROS), whereas high-dose (10µg/mL) priming resulted in opposing reactions marked by increased IL-10 and suppressed pro-inflammatory mediators upon a second stimulus. A similar pattern of pro-inflammatory activation (trained sensitivity) and anti-inflammatory properties (tolerance) was recapitulated in cellular functional in vitro assays (transmigration and phagocytosis). Priming by LTA correlated with TLR2/MyD88-mediated regulation of NFκB-p65 through intermediate PI3Ks/MAPK. Collectively, our data suggest a previously unknown capacity of neutrophils to be differentially primed by varying doses of LTA, endorsing memory-like features in neutrophils.
Gesehen am 13.07.2022